Menstimulasi Tingkat Kepercayaan Diri Pada Anak Dengan Metode Bermain Peran - Febrianti, Sonia Dita Anggraeni; Hamzah, Nur; Sapendi, Sapendi (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Negeri Pontianak, 2021)
Early childhood education is a process of fostering development and development of children at birth as a whole, which includes appropriate and correct social, emotional, moral, and spiritual aspects so that children can grow and develop optimally. Play for early childhood can learn and learn many things, be able to recognize rules, socialize, place themselves, organize emotions, tolerance, cooperation and uphold sportsmanship. Based on the results of observations, the social emotional aspects of the child have not developed optimally. The purpose in this is to see the implementation of the role play program in improving social, emotional, moral, and spiritual children. Observation data through and interviews. Based on the results of observations, it shows that in the implementation of role playing in improving the social emotional of children are as follows: the teacher collects the children to be given directions and rules in the game, the teacher talks about the tools the children will use to play, the teacher gives the assignment before play and attendance and count the number of children together, the teacher only joins and accompanies the child in role playing, the teacher has discussions about role playing that have been implemented.